Agricultural input retailers in Myanmar: Insights from the 2025 monsoon season - Goeb, Joseph; Htar, May Thet; Zu, A Myint (International Food Policy Research Institute, 2025)
This Research Note presents results from an August 2025 phone survey of 227 agricultural input retailers – who provide agricultural inputs and informal credit to farmers – in Myanmar’s major agro-ecological zones. Key Findings • Input sales declined sharply in the 2025 monsoon relative to 2024. Fewer retailers sold inorganic fertilizers and pesticides, and aggregate sales for those who did sell declined by 31 percent for inorganic fertilizer and 10 percent for pesticides. • The decline is not solely due to supply shortages: smaller areas planted, weaker farm profits, and conflict have dampened demand, while climate change and the 2025 earthquake add to input market stress. Two-thirds of retailers cite lower input demand from climate change in the past three years, and earthquake impacts – while more localized – disrupted market access and areas planted. • Transport remains the dominant business disruption. Even with a slight drop in overall reported disruptions compared to 2024, transport problems – higher costs, checkpoints and roadblocks – still dominate. Long input supply chains dependent on imports and flowing through Yangon mean that checkpoints and higher costs compound as inputs reach rural farmers. • Farmer finances are stressed, especially in rice-dominant areas. Farmers are asking for and taking more credit from input retailers. This likely reflects tighter liquidity following the recent global rice price decline, which has reduced incentives and profitability for monsoon paddy. • Credit provision is expanding but adding risk. More retailers are providing credit to farmers and sourcing their inputs on credit from suppliers. Yet, two-thirds of retailers that provided credit in 2024 still have unpaid debts from farmers, raising the risks of cascading financial stress. • Measures to ease transport constraints, stabilize access to imported fertilizers and pesticides, and expand formal credit options for both farmers and retailers would help sustain this essential link in the agrifood system.